Improved Sentinel Method for Surveillance and Collection of Filth Fly Parasitoids. Issue 6 (2nd November 2020) - Geden, Christopher J; Johnson, Dana M; Taylor, David B
Abstract: Parasitoids are important natural enemies of house flies and other muscoid flies. The two most commonly used methods for collecting fly parasitoids from the field have distinct advantages and disadvantages. Collections of wild puparia depend on the ability to find puparia in sufficient numbers and are prone to localized distortions in relative species abundance because of the overrepresentation of samples from hot spots of fly larval activity. Placement and retrieval of sentinel puparia is convenient and allows consistent sampling over time but is strongly biased in favor of Muscidifurax spp. over Spalangia spp. An improved sentinel method is described that combines some of the advantages of these two methods. Fly medium containing larvae is placed in containers, topped with a screen mesh bag of puparia, and placed in vertebrate-proof wire cages. Cages are placed at sites of actual or potential fly breeding and retrieved 3–7 d later. The modified method collected species profiles that more closely resembled those of collections of wild puparia than those from sentinel pupal bags. A method is also described for isolating puparia individually in 96-well tissue culture plates for parasitoid emergence. Use of the plate method provided a substantial saving of time and labor over the use of individual gelatin capsules for pupal isolation. Puparia from the collections that were housed individually in the wells of tissue culture plates had a higher proportion of emerged Spalangia species than puparia that were held in groups.